Energy dispersive x-ray analysis in the study of pneumoconiosis. Issue 2 (May 1977) - Funahashi, A; Siegesmund, K A; Dragen, R F; Pintar, K
Abstract : Identification of inorganic substances in the lung is an important step towards the establishment of a cause and effect relationship in the study of pneumoconiosis. The conventional methods for this identification usually require an ashing which makes it difficult to study the localisation of these substances in relation to pathology. A method is described to identify foreign substances in the tissue obtained either on biopsy or autopsy without destroying them. The technique employs scanning electron microscopy together with energy dispersive x-ray analysis. This method not only allows simultaneous multi-elemental analysis of over 80 elements, but also permits detailed morphological examination while the tissue is being analysed.